Fabrication of Mesoporous V2O5@g-C3N4 Nanocomposite as Photocatalyst for Dye Degradation - Sayed M. Saleh; Abuzar E. A. E. Albadri; Mohamed Ali Ben Aissa; Abueliz Modwi (Crystals, 2022)
This study investigated the photocatalytic degradation of RB dye by V2O5@g-C3N4 nano-catalysts. The sonication method was utilized to create V2O5@g-C3N4 nano-catalysts. V2O5@g-C3N4 nano-catalysts were characterized using X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), high-resolution electron microscopy (TEM), BET-surface area analyzer, X-ray photoelectron spectroscopy (XPS), and ultraviolet spectroscopy. In the meantime, the photocatalytic activity, pH, and photocatalyst dosage are investigated in depth to account for RB dye decolorization. The rate constant for RB dye photodegradation was 0.0517 (min−1) and the decolorization rate was 93.4%. The degrading efficiency of RB dye by V2O5@g-C3N4 nanocatalysts is consistent with pseudo-first-order kinetics. The results of this study demonstrated that V2O5@g-C3N4 nanocatalysts are particularly effective at destroying dyes in water.